Changes in SedLine-derived processed electroencephalographic parameters during hypothermia in patients undergoing cardiac surgery with cardiopulmonary bypass - Belletti, Alessandro; Lee, Dong-Kyu; Yanase, Fumitaka; Naorungroj, Thummaporn; Eastwood, Glenn M.; Bellomo, Rinaldo; Weinberg, Laurence (Frontiers in Cardiovascular Medicine, 2023)
Objective: Processed electroencephalography (pEEG) is used to monitor depth-of-anesthesia during cardiopulmonary bypass (CPB). The SedLine device has been recently introduced for pEEG monitoring. However, the effect of hypothermia on its parameters during CPB is unknown. Accordingly, we aimed to investigate temperature-induced changes in SedLine-derived pEEG parameters during CPB. Design: Prospective observational study Setting: Cardiac surgery operating theatre Participants: 28 patients undergoing elective cardiac surgery with CPB Interventions: We continuously measured patient state index (PSI), suppression ratio (SR), bilateral spectral edge frequency (SEF) and temperature. We used linear mixed modelling with fixed and random effects to study the interactions between pEEG parameters and core temperature. Measurements and Main Results: During CPB maintenance, the median temperature was 32.1°C (interquartile range [IQR]: 29.8–33.6) at the end of cooling and 32.8°C (IQR: 30.1–34.0) at rewarming initiation. For each degree Celsius change in temperature during cooling and rewarming the PSI either decreased by 0.8 points (95% confidence interval [CI] 0.7–¬1.0; p<0.001] or increased by 0.7 points (95% CI 0.6¬–0.8; p<0.001). The SR increased by 2.9 (95% CI 2.3–¬3.4); p<0.001) during cooling and decreased by 2.2 (95% CI 1.7¬–2.7; p<0.001) during rewarming. Changes in the SEF were not related to changes in temperature. Conclusions: During hypothermic CPB, temperature changes led to concordant changes in the PSI. The SR increased during cooling and decreased during rewarming. Clinicians using SedLine for depth-of-anesthesia monitoring should be aware of these effects when interpreting the PSI and SR values.